2020
DOI: 10.1108/et-09-2019-0209
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed experiential learning to meet ever-changing entrepreneurship demands

Abstract: PurposePolicy makers have called for more entrepreneurship throughout societies as a response to the digital transformation. This paper argues that the rapidly changing conditions of the digital age indeed mark a change in the bases of entrepreneurship. Specifically, as adaptivity becomes key, a learning capacity and general ability to adapt becomes a critical factor in entrepreneurial activity. The paper identifies self-directed learning (SDL) as a fundamental competence in this regard and examines its role f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…, 2016) as well. This proposed relationship is supported in previous review studies by Tseng (2013) and Morris and Konig (2020), which found that self-directed learning can enhance entrepreneurial knowledge and experiences within the entrepreneurial development process.…”
Section: Prior Literaturesupporting
confidence: 76%
“…, 2016) as well. This proposed relationship is supported in previous review studies by Tseng (2013) and Morris and Konig (2020), which found that self-directed learning can enhance entrepreneurial knowledge and experiences within the entrepreneurial development process.…”
Section: Prior Literaturesupporting
confidence: 76%
“…So HEIs have understood the need to create a type of education where individuals' self-directed learning must be a fundamental competence (Morris & K€ onig, 2020). Entrepreneurship education should allow the development of new behaviors, habits and beliefs (Daniel, 2016) in teaching that allows knowledge sharing.…”
Section: Inmrmentioning
confidence: 99%
“…This knowledge sharing causes, in the digital entrepreneur, the need to develop specific knowledge and competencies to face new business challenges, meaning they need to use selflearning strategies (Young, 2007). It is a fundamental competence for entrepreneurship (Morris and K€ onig, 2020). In this case, digital platforms can help to interlink academia and entrepreneurs in self-learning, updating their theoretical knowledge (Linzalone et al, 2020).…”
Section: Pillar 3knowledge Sharingmentioning
confidence: 99%
“…In such conditions, which have been exacerbated by the COVID-19 pandemic (Enriquez and Gargiulo, 2022), from an economic perspective, creativity has been positioned as a critical workplace competence (European Commission, 2015; Shumylo et al , 2022; OECD, 2022). I should highlight the point here that generating creative solutions is important in many professional fields, such as medicine, teaching, informatics, business, engineering and entrepreneurship (Morris and König, 2021; Davis, 2012; Ma et al , 2018; OECD, 2022).…”
Section: Introductionmentioning
confidence: 99%